Pendampingan Guru dalam Penguatan Literasi Bahasa dan Gender untuk Pencegahan Kekerasan Verbal di Lingkungan SDN 2 Sukowilangun, Kecamatan Kalipare, Kabupaten Malang - Usrin Malikha (Lembaga Penerbitan dan Publikasi Ilmiah, 2026)
Teachers’ language use in the classroom greatly influences the creation of a conducive, inclusive, and violence-free learning environment, free from verbal abuse and gender bias. This study at SDN 2 Sukowilangun aims to enhance teachers’ competence in using educational and child-friendly language through training in nonviolent communication and gender literacy. The mentoring results indicate positive changes in teachers’ communication patterns, a calmer classroom atmosphere, and increased student participation. Participant evaluations show improved understanding and commitment to applying communication practices that are free from violence and gender bias. This activity makes a significant contribution to building a safe and inclusive primary education environment. Penggunaan bahasa guru dalam pembelajaran sangat memengaruhi suasana kelas yang kondusif, inklusif, dan bebas kekerasan verbal serta bias gender. Studi di SDN 2 Sukowilangun bertujuan meningkatkan kompetensi guru dalam penggunaan bahasa edukatif dan ramah anak melalui pelatihan komunikasi nonviolent dan literasi gender. Hasil pendampingan menunjukkan perubahan positif dalam pola komunikasi guru, suasana kelas yang lebih tenang, serta meningkatnya partisipasi siswa. Evaluasi peserta mengindikasikan pemahaman dan komitmen yang meningkat untuk menerapkan komunikasi bebas kekerasan dan bias gender. Kegiatan ini memberikan kontribusi penting dalam menciptakan pendidikan dasar yang aman dan inklusif.